Cote d’Ivoire 10th Economic Update : Cote d’Ivoire and the COVID-19 Pandemic - World Bank (World Bank, Washington, DC, 2020)
This report contributes to the growing body of knowledge by shedding light on the impact of COVID-19 and confinement measures on Ivoirian enterprises and households. It builds on two dedicated sets of survey data that were collected in April 2020, at the height of the local confinement measures. The report also presents a set of policy recommendations, building on the government’s response plan and how it addresses the triple challenge of saving lives, protecting livelihoods and protecting the future. Specifically, it tries to highlight responses measures that could also contribute to boosting recovery and support the country’s return to strong growth. The report begins in Part one with a presentation of the country’s progress in 2019, recent developments in 2020 and the macroeconomic outlook. Thanks to strong economic growth and sound macroeconomic policies, Cote d’Ivoire entered the crisis from a position of strength. However, the global recession and uncertain evolution of the domestic outbreak pose significant downside risks. Part two is then dedicated to a diagnostic of COVID 19’s impact on enterprises and households. The new survey data suggests that enterprises across all sectors felt the crisis impact, in terms of closures, sales, disruptions in logistics and access to inputs. Smaller enterprises with less buffers to withstand shocks were more severely impacted than larger ones. Households likewise reported much reduced working hours and a significant drop in incomes, salaries or revenues, while being (temporarily) hit with higher prices for food. Taken together, the survey data suggests that a severe shock for consumption and demand will become visible and tangible in the next months, even as the overall situation appears to have stabilized.